αCGRP-Induced Changes in Cerebral and Systemic Circulation; A TCD Study - Visočnik, Darja; Žvan, Bojana; Zaletel, Marjan; Zupan, Matija (Frontiers in Neurology, 2020)
It is known that perivascular application of CGRP induces cerebral vasodilatation. However, it is unclear whether intravenous alfa CGRP (αCGRP) induces changes in cerebral and systemic hemodynamics. Therefore, we studied the influence of an αCGRP intravenous infusion at a rate of 1.5 mcg/min in 20 min on mean arterial velocity in the middle cerebral artery (vm MCA) and in the posterior cerebral artery (vm PCA) in twenty healthy subjects using transcranial Doppler (TCD). We found out that αCGRP decreased vm MCA (p<0.001), vm PCA (p < 0.001), mean arterial pressure (MAP) (p< 0.001) and end-tidal CO2 (Et-CO2) (p=0.030). The heart rate (HR) increased during αCGRP infusion (p<0.001). In addition, we found a positive relationship between Et-CO2 and vm MCA (p=0.001) as well as vm PCA (p=0.043). In our view, αCGRP induces changes in cerebral and systemic circulation in healthy volunteers. It might cause vasodilatation of MCA and PCA and a compensatory decrease of Et-CO2 to αCGRP related hemodynamic changes.